PROMOSI KESEHATAN DENGAN FILM PENDEK TENTANG PENCEGAHAN STUNTING PADA KADER DI DESA TANJUNG PAUH KM. 32 KAB. MUARO JAMBI TAHUN 2024 - pahrur razi; Nopindra, alpari; Surayah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Stunting cases in Indonesia, especially in Jambi Province, require efforts to increase knowledge and skills in stunting prevention. Various efforts to promote stunting prevention have been initiated by the government to improve stunting prevention. Intensive health education efforts should be carried out with various innovations in the use of IT to improve knowledge and skills in stunting prevention, such as through short films. The purpose of this PKM is to improve knowledge and skills in stunting prevention and to test the effectiveness of community service interventions through health promotion with short films on stunting prevention. Data collection from primary data obtained from questionnaires and observation formats. This PKM will be carried out in April-October 2024 with 80 participants. The results obtained increased knowledge and skills in stunting prevention in cadres in Tanjung Pauh Village, Km. 32, Muaro Jambi Regency in 2025 from 25% (pre-test) to 100% (post-test). It is recommended to routinely increase stunting prevention.